Evaluating the impact of a universal FRIENDS for Life Programme on emotional distress and academic self-perceptions - Paul, Julie (2011)
FRIENDS For Life' (Barrett, 2004) is a ten-week programme for children aged 7 - 11 years, based on cognitive behavioural principles, designed to teach coping skills and techniques to manage anxiety and depression. This study describes an evaluation of a universal programme, delivered to a class of Year 5 children in a school in a socio-economically disadvantaged community located in the East of England.